Engineered TCR-T Cell Immunotherapy in Anticancer Precision Medicine: Pros and Cons - Zhao, Qijie; Jiang, Yu; Xiang, Shixin; Kaboli, Parham Jabbarzadeh; Shen, Jing; Zhao, Yueshui; Wu, Xu; Du, Fukuan; Li, Mingxing; Cho, Chi Hin; Li, Jing; Wen, Qinglian; et al. (Frontiers in Immunology, 2021)
This review provides insight into the role of engineered T-cell receptors (TCRs) in immunotherapy. Novel approaches have been developed to boost anticancer immune system, including targeting new antigens, manufacturing new engineered or modified TCRs, and creating a safety switch for endo-suicide genes. In order to re-activate T cells against tumors, immune-mobilizing monoclonal TCRs against cancer (ImmTAC) have been developed as a novel class of manufactured molecules which are bispecific and recognize both cancer and T cells. The TCRs target special antigens such as NY-ESO-1, AHNAKS2580F or ERBB2H473Y to boost the efficacy of anticancer immunotherapy. The safety of genetically modified T cells is very important. Therefore, this review discusses pros and cons of different approaches, such as ImmTAC, Herpes simplex virus thymidine kinase (HSV-TK), and inducible caspase-9 in cancer immunotherapy. Clinical trials related to TCR-T cell therapy and monoclonal antibodies designed for overcoming immunosuppression, and recent advances made in understanding how TCRs are additionally examined. New approaches that can better detect antigens and drive an effective T cell response are discussed as well.